FILIAL SELF-EFFICACY BASED ON QUALITY OF RELATIONSHIP WITH PARENTS AND GENDER - Qonitatin, Novi; Abidin, Zaenal; Nurhayati, Niken Fatimah (Faculty of Psychology, Universitas Diponegoro, 2022)
The belief of adolescents to fulfill their role as a child in the family known as filial self-efficacy that assumed to provide a feeling of being able to organize events in carrying out their life as part of the family. The purpose of this study was to empirically examine the relationship between the quality of the adolescent’s relationship with parents and filial self-efficacy, and differences in filial self-efficacy based on gender. Research participants were 93 students of the Faculty of Psychology Universitas Diponegoro, who were in the late adolescence age range (18-22 years), consisting of 28 boys (30%) and 65 girls (70%). The data were obtained using the Filial SelfEfficacy Scale based on Bandura’s perspective and the Adolescent-Parent Relationships Scale based on the Grotevant and Cooper perspective. The analysis technique used is product moment analysis and t-test. The results showed that there was a significant positive relationship between the quality of the relationship between adolescents and their parents and filial self-efficacy as indicated by a correlation coefficient of .783 (p > .01). This means that the more positive the quality of the relationships that exist between adolescents and their parents, the higher the filial self-efficacy. Conversely, the more negative the quality of the relationship between adolescents and their parents, the lower the filial self-efficacy. According to the research, there was no significant difference in filial self-efficacy between boys and girls, with a t-count of -0.029 and a significance value of .977 (p > .05).